Cutaneous hypersensitivity induced in rabbits by extracts of the tick Amblyomma cajennense (Acari: Ixodidae) - Hlatshwayo, M.; Szabó, M. J.P.; Bechara, G. H.; Mbati, P. A. (South African Vet Assn, 2004)
The cutaneous hypersensitivity test was used to correlate host resistance to ticks and type of reactions elicited by Amblyomma cajennense (Fabricius, 1787) tick extract in rabbits. Rabbits were divided into 3 groups of 2 animals each: naive, pre-infested and control. Cutaneous hypersensitivity was induced by intradermal inoculation of 25 μg extract in 0.03 ml of phosphate buffered saline (PBS) in rabbit ears. Control rabbits were inoculated with PBS only. The ear thickness was measured with a Mitutoyo® device before and 10 min, 1, 2, 4, 18, 24, 48, 72 and 96 h post-inoculation (PI). Pre-infested rabbits showed an immediate type reaction within the 1st 10 min PI (60% increase in ear thickness) and a delayed reaction (18 h) (85 % increase), whereas the naive rabbits showed only the immediate reaction within the 1st 4 h (60 % increase). PBS induced only mild reactions. These results point out the crucial role of the cellular immune response of rabbits in the expression of resistance to A. cajennense.
Keywords: Amblyomma cajennense; Cutaneous hypersensitivity; Tick extract